Self-healing and self-adhesion type metal protective film based on multi-scale micro-nano fiber network and preparation method of self-healing and self-adhesion type metal protective film

Through the self-healing polyvinylidene fluoride film with a multi-scale micro-nanofiber network structure, the existing self-healing membrane materials have solved the problem of slow media outflow and limited repair times in steel structure protection, and achieved rapid self-self at room temperature Healing and multiple repairs are suitable for repairing cracks of different sizes, improving the overall performance of the material.

CN119193014APending Publication Date: 2024-12-27RAILWAY CONSTR RES INST OF CHINA ACAD OF RAILWAY SCI CO LTD +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411240323.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing self-healing membranes face the problems of slow flow of repair media, specific conditions, limited repair times and a single size, and it is difficult to cope with multiple cracking forms in multiple repeated repairs and cracks of different sizes. Repair requirements.

Method used

Self-healing polyvinylidene fluoride film with a multi-scale micro-nanofiber network structure is used to prepare core-shell structure micro-nanofibers by coaxial electrospinning, combining fluorocarbon resin and micro-foam polyurethane to form rapid self-healing and multi-polyurethane. protective film with repeated repair capability.

Benefits of technology

It realizes rapid closing of cracks at room temperature and repeated repairs multiple times, with excellent mechanical properties and durability, and is suitable for self-healing of cracks from microscopic to macroscopic, significantly improving the comprehensive performance of self-healing materials.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a self-healing and self-adhesion type metal protective film based on a multi-scale micro-nano fiber network and a preparation method of the self-healing and self-adhesion type metal protective film. The self-adhesive protective film is a self-adhesive film material which is prepared from a self-healing polyvinylidene fluoride film containing a multi-scale micro-nano fiber network, a self-adhesive glue layer and a release film layer through melt-blowing, rolling and compounding and has self-healing and long-term protection performance. A multi-scale core-shell fiber network containing a micro-foaming polyurethane core material prepared by using a coaxial electrostatic spinning technology is used as a self-healing material, so that the filling enhancement of a membrane material is realized, the healing response to cracks of different scales can be generated, the healing effect is excellent, and the cost is low as the use amount of the core material for single-time healing is small. The self-adhesive film can repeatedly realize the self-healing process of multiple times of cracking. The self-adhesive film material has excellent adhesion, durability and self-healing performance, is suitable for durable repair and long-term protection of steel structures, and has important significance for related technical progress and industrial development.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of fine polymer materials, and specifically relates to the preparation of a self-healing self-adhesive metal protective film based on a multi-scale micro-nano fiber network and its application in the field of metal structure protection and repair. Background Art

[0002] Due to the advantages of light weight, high strength, and easy construction and installation, steel structures occupy an important position in the construction process of large bridges, factories, venues and other building structures. Corrosion damage is the most important form of damage to steel structures, which will lead to a reduction in the cross-sectional area of ​​steel components, a decrease in bearing capacity, and a decrease in the service life of the structure. According to statistics, the cost of anti-corrosion and repair of steel structure buildings will account for more than 20% of the total construction cost. Although steel structures are all treated with anti-corrosion, many steel structures, especially steel bridges, are erected in harsh environments such as the ocean, acid rain, and industrial corrosion. They are subjected to external loads and are affected by various factors such as sulfates, rain, condensation, seawater, and typhoons. Anti-corrosion measures based on coatings often cause local damage and destruction under the effects of environmental erosion, external forces, and stress fatigue, and must be repaired in a timely manner. The main means of repair at present is the re-coating of protective coatings, but the re-coating process is complicated, the working hours are long, and the cost is high. The repair technology for small local damage is less economical and has lower work efficiency. Small-scale on-site construction is also difficult to control, and the quality of repair is difficult to guarantee.

[0003] The self-adhesive film is a protective film material that can be attached to a substrate and is prepared by using a prefabricated film material as a protective material and a composite self-adhesive adhesive on the back as an adhesive material. Because it uses a prefabricated film material, the film quality, barrier properties and durability are significantly better than the coating formed by on-site reaction film, and no curing time is required, it takes effect immediately and is easy to operate. Therefore, the use of prefabricated self-adhesive films for the repair of corrosion damage to steel structures has a high research value. For example, patent CN112831121B discloses a PVDC high-barrier co-extruded self-adhesive film for military protection. The electromagnetic shielding effect of the film is improved by adding modified graphene, the water vapor permeability is low, and the pressure resistance stability is strong, which meets the military protection needs.

[0004] During the long-term service of the protective film, if it encounters external force damage or long-term stress aging conditions, it may cause the film material to crack, making the protection ineffective. Therefore, it is of great research significance for the long-term service of the self-adhesive film material to give the self-healing property of damage through relevant technical means. There are currently two main modes of commonly used self-healing technology. One is to introduce non-covalent effects or dynamic covalent bonds into the membrane material itself to enable it to have self-healing ability under special conditions, but this repair method requires specific conditions and the process is slow. Introducing microcapsules or fibers loaded with repair functional materials into the membrane material, and releasing the repair medium under the condition of membrane cracking to achieve self-repair is a more feasible self-healing solution. For example, patent CN115387030A discloses a self-repairing core-shell nanofiber membrane. By using self-repairing polyurethane as the fiber core layer, a self-repairing nanofiber membrane is prepared by coaxial electrospinning, which can achieve self-repair of the damaged part. Patent CN103755156B discloses a self-healing film based on layer-by-layer assembly of hollow multi-layer nanocapsules. By cyclically depositing branched polyacetimide, polyacrylic acid and hollow microcapsules on the glass surface layer by layer, a hollow multi-layer nanocapsule self-healing film is prepared. The film has extremely strong self-repairing ability and can heal quickly under water-induced conditions.

[0005] From the above description, it can be seen that the self-healing membrane materials that have been studied so far have certain practical value. However, from the perspective of the overall development of technology, the use of self-healing membrane materials for the protection and repair of steel structures still faces some problems. First, the outflow of the repair medium usually relies on capillary action, the healing process is slow and requires specific conditions, and the repair medium is consumed in large quantities during the repair process, which makes it difficult to meet the needs of repeated repairs. In addition, in actual use, protective membrane materials face a variety of cracking forms from microscopic to macroscopic, and repair materials of a single size and form are difficult to achieve the release of repair media under all conditions. Therefore, based on relevant research, further developing new self-healing membrane materials, improving the self-healing ability to cope with multiple cracks and cracks of different sizes, and improving the comprehensive performance of self-healing membrane materials are of great significance for promoting the further development of the application of self-adhesive membrane materials in the field of metal corrosion protection and promoting the progress of related industries. . Summary of the invention

[0006] The purpose of the present invention is to solve the above problems and provide a self-healing and self-adhesive metal protective film based on a multi-scale micro-nano fiber network and a preparation method thereof.

[0007] The self-healing and self-adhesive metal protective film based on a multi-scale micro-nano fiber network described in the present invention is a protective film material with self-adhesive properties composed of a self-healing polyvinylidene fluoride film containing a multi-scale micro-nano fiber network, a self-adhesive layer and a release film layer; wherein the multi-scale micro-nano fiber network is composed of micro-nano fibers with a core-shell structure prepared by coaxial electrospinning using fluorocarbon resin as wall material, a micro-foamed polyurethane main agent and a curing agent as core materials respectively; wherein the fiber diameter size distribution in the multi-scale micro-nano fiber network is (50~200) nm:(200~800) nm: (1000~2000) nm=2:5:3.

[0008] The preparation method of the multi-scale micro-nano fiber network in the self-healing self-adhesive metal protective film is as follows: (1) taking the micro-foamed polyurethane main agent as the core layer spinning solution A, the micro-foamed polyurethane curing agent as the core layer spinning solution B, and the fluorocarbon resin solution as the shell layer spinning solution C; (2) The core layer spinning solution A and the shell layer spinning solution C were placed into the core layer syringe and the shell layer syringe of the coaxial electrospinning machine and connected to the needle for coaxial electrospinning. Under the condition of a fixed feed rate of C solution at (0.95-1.05) mL / h, the feed rate of A solution was adjusted to (0.05-0.10) mL / h, (0.15-0.25) mL / h and (0.35-0.45) mL / h to prepare core-shell structured micro-nanofibers d1-d3 with diameter distributions of (50-200) nm, (200-800) nm and (1000-2000) nm respectively. (3) Using core layer spinning solution B instead of core layer spinning solution A, referring to step (2), prepare core-shell structured micro-nanofibers e1~e3 containing curing agent components of different sizes with diameter distributions ranging from (50~200) nm, (200~800) nm and (1000~2000) nm.

[0009] (4) The multi-scale core-shell structured micro-nanofibers d1-d3 and e1-e3 were heated at 80°C for 4 h to obtain multi-scale core-shell structured micro-nanofibers D1-D3 and E1-E3 with a cross-linked shell structure.

[0010] (5) Weigh the micro-nano fibers D1-D3 as D in a ratio of 2:5:3, weigh the micro-nano fibers E1-E3 as E in a ratio of 2:5:3, mix D and E in a ratio of 1:(0.9-1.2), immerse them in ethanol and mix and disperse them evenly, and then dry them in a vacuum oven to obtain a multi-scale micro-nano fiber network.

[0011] The micro-foamed polyurethane main agent in the preparation method of the multi-scale core-shell structure micro-nano fiber is prepared by uniformly dispersing polyether polyol, foam stabilizer, catalyst and water through high-speed stirring, wherein the amounts of foam stabilizer, catalyst and water are 0.5-2%, 0.05-0.5% and 0.1-0.5% respectively, calculated on the mass of polyether polyol; wherein the polyether polyol is at least one of trifunctional hydrophobic polyether polyols with a relative molecular mass of 300-1200, the foam stabilizer is a polysiloxane foam stabilizer, and the catalyst is at least one of A33 and T12; the micro-foamed polyurethane curing agent is toluene diisocyanate, isophorone diisocyanate, p-phenylene diisocyanate, toluene The invention relates to a fluorocarbon resin solution comprising at least one of diisocyanate, toluene diisocyanate trimer, hexamethylene diisocyanate trimer and hexamethylene diisocyanate biuret; the fluorocarbon resin solution comprises a fluorocarbon resin, a latent curing agent and a solvent, wherein the contents of the fluorocarbon resin, the latent curing agent and the solvent are 12-16%, 3-4% and 80-85% respectively; the fluorocarbon resin is at least one of polyvinylidene fluoride resin, polytrifluorochloroethylene-vinyl ether resin and polytetrafluorochloroethylene-vinyl ether resin; the latent curing agent is a thermally dissociated latent curing agent; and the solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide and acetone.

[0012] In the coaxial electrospinning process of the preparation method of the multi-scale core-shell structured micro-nano fibers, the spinning distance is 12-20 cm, the spinning voltage is 11-18 kV, the ambient temperature is 20-28° C., and the ambient humidity is 30%-70% RH.

[0013] The self-healing polyvinylidene fluoride film containing a multi-scale micro-nano fiber network in the self-healing self-adhesive metal protective film based on a multi-scale micro-nano fiber network is a film obtained by co-extrusion molding of the multi-scale micro-nano fiber network and the polyvinylidene fluoride resin; the amount of the multi-scale micro-nano fiber network is 2-5% of the amount of the polyvinylidene fluoride resin; the film thickness is 0.5-1.5 mm.

[0014] The preparation method of the self-healing self-adhesive metal protective film based on a multi-scale micro-nano fiber network is as follows: (1) tensioning the release film and melt-blowing a hot-melt pressure-sensitive adhesive on the release film; (2) compounding it with a self-healing polyvinylidene fluoride film containing a multi-scale micro-nano fiber network, and rolling it together to obtain a self-healing self-adhesive metal protective film based on a multi-scale micro-nano fiber network.

[0015] The release film in the preparation method is one of a polyolefin release film, a polyimide release film, and a polyester release film; the hot melt pressure-sensitive adhesive is one of a polyacrylic acid hot melt pressure-sensitive adhesive, a polyolefin hot melt pressure-sensitive adhesive, a polystyrene hot melt pressure-sensitive adhesive, and a butyl rubber hot melt pressure-sensitive adhesive.

[0016] The self-healing and self-adhesive metal protective film based on the multi-scale micro-nano fiber network can be used as a protective material or rust repair material for steel structure bridges, factory buildings, curtain walls and other building structures. The positive effects of the self-healing self-adhesive metal protective film based on a multi-scale micro-nano fiber network of the present invention are: The self-adhesive metal protective film prepared in the present invention achieves long-term and durable protection of steel structures by fixing PVDF membrane materials with self-healing properties on the surface of steel structures using high-adhesive self-adhesive glue. The multi-scale micro-nano core-shell fiber network in the PVDF membrane is the key to the present invention. The core layer of the core-shell fiber uses a micro-foamed polyurethane main agent and a curing agent as a self-healing medium, which has a good self-healing effect and a fast reaction rate at room temperature, and can quickly seal the cracks. In addition, due to its 80%-200% micro-expansion performance, on the one hand, it can achieve dense filling of cracks to prevent the entry of external corrosive media, and on the other hand, only a small amount of self-healing medium is used to repair the cracks, and multiple large-scale self-healing processes can be achieved, and the effect is excellent. The shell layer of the core-shell fiber uses fluorocarbon resin, which has good durability and good compatibility with PVDF membrane materials, and can be evenly distributed in the PVDF membrane material. In addition, by formulating a micro-nano fiber network structure with a suitable size ratio, on the one hand, it plays a filling and reinforcing role inside, avoiding the weakening of the mechanical properties of the membrane material by conventional self-healing capsules. On the other hand, it has the ability to self-heal and respond to cracks of different sizes from micro to macro. Since fibers of different sizes are obtained by adjusting the core-shell injection ratio in coaxial electrospinning, the content of self-healing core material in the core-shell fiber increases with the increase of size, thereby achieving rapid repair of cracks of different sizes, which has significant advantages over the self-healing performance of conventional self-healing materials.

[0017] From the above description, it can be seen that the self-healing self-adhesive protective film technology has a clear mechanism of action, a simple production process, excellent product performance, strong durability, low cost, and can be used in large-scale production. It is of great significance for the preparation and research and development of surface protective materials with self-healing functions and their promotion in related application fields. DETAILED DESCRIPTION

[0018] The present invention is further described in detail below with reference to specific embodiments.

[0019] Example 1: A self-healing self-adhesive metal protective film I based on a multi-scale micro-nano fiber network, the preparation process of which is as follows: (1) 100 parts of a trifunctional polyether polyol with a molecular weight of 500, 1.6 parts of a polysiloxane foam stabilizer, 0.1 parts of a T12 catalyst, 0.2 parts of an A33 catalyst and 0.4 parts of water were uniformly dispersed by high-speed stirring as the core layer spinning solution AI, isophorone diisocyanate was used as the core layer spinning solution BI, 14 parts of a polyvinylidene fluoride resin, 3.5 parts of a thermal dissociation type latent curing agent and 82.5 parts of N,N-dimethylformamide were mixed uniformly as the shell layer spinning solution CI; (2) The core layer spinning solution AI and the shell layer spinning solution CI were placed into the core layer syringe and the shell layer syringe of the coaxial electrospinning machine and connected to the needle for coaxial electrospinning. Under the condition of a fixed CI solution feeding rate of 1.0 mL / h, the AI ​​solution feeding rate was adjusted to 0.06 mL / h, 0.2 mL / h and 0.42 mL / h to prepare core-shell structured micro-nanofibers d1I~d3I with diameter distributions of (50~200) nm, (200~800) nm and (1000~2000) nm, respectively. (3) Using core layer spinning solution BI instead of core layer spinning solution AI, referring to step (2), prepare core-shell structured micro-nanofibers e1I~e3I containing curing agent components of different sizes with diameter distributions ranging from (50~200) nm, (200~800) nm and (1000~2000) nm.

[0020] (4) The multi-scale core-shell structured micro-nanofibers d1I~d3I and e1I~e3I were heated at 80°C for 4 h to obtain multi-scale core-shell structured micro-nanofibers D1I~D3I and E1I~E3I with shell cross-linked structures.

[0021] (5) Weigh the micro-nanofibers D1I to D3I as DI at a ratio of 2:5:3, weigh the micro-nanofibers E1I to E3I as EI at a ratio of 2:5:3, mix DI and EI at a ratio of 1:0.95, immerse them in ethanol and mix and disperse them evenly, and then dry them in a vacuum oven to obtain a multi-scale micro-nanofiber network I.

[0022] (6) 2.5 parts of the multi-scale micro-nano fiber network I and 97.5 parts of polyvinylidene fluoride resin were co-extruded to obtain a self-healing polyvinylidene fluoride film I with a thickness of 0.8 mm.

[0023] (7) The self-healing polyvinylidene fluoride film I is melt-blown and roller-pressed with a polyolefin release film and a polyacrylic hot-melt pressure-sensitive adhesive to obtain a self-healing self-adhesive metal protective film I based on a multi-scale micro-nano fiber network.

[0024] Example 2: A self-healing self-adhesive metal protective film II based on a multi-scale micro-nano fiber network, the preparation process of which is as follows: (1) 100 parts of a trifunctional polyether polyol with a molecular weight of 700, 1.1 parts of a polysiloxane foam stabilizer, 0.1 parts of a T12 catalyst, 0.1 parts of an A33 catalyst and 0.3 parts of water are uniformly dispersed by high-speed stirring as a core layer spinning solution AII, toluene diisocyanate is used as a core layer spinning solution BII, 15 parts of a polytrifluorochloroethylene-vinyl ether resin, 3.8 parts of a thermally dissociated latent curing agent and 81.2 parts of N,N-dimethylacetamide are mixed uniformly as a shell layer spinning solution CII; (2) The core layer spinning solution AII and the shell layer spinning solution CII were placed into the core layer syringe and the shell layer syringe of the coaxial electrospinning machine and connected to the needle for coaxial electrospinning. Under the condition of a fixed CII solution feed rate of 1.0 mL / h, the feed rate of AII solution was adjusted to 0.06 mL / h, 0.2 mL / h and 0.42 mL / h to prepare core-shell structured micro-nanofibers d1II~d3II with diameter distributions of (50~200) nm, (200~800) nm and (1000~2000) nm, respectively; (3) Using the core layer spinning solution BII instead of the core layer spinning solution AII, referring to step (2), prepare core-shell structured micro-nanofibers e1II~e3II containing a curing agent component with diameter distributions of (50~200) nm, (200~800) nm and (1000~2000) nm of different sizes.

[0025] (4) The multi-scale core-shell structured micro-nanofibers d1II~d3II and e1II~e3II were heated at 80°C for 4 h to obtain the multi-scale core-shell structured micro-nanofibers D1II~D3II and E1II~E3II with shell cross-linked structures.

[0026] (5) Weigh the micro-nanofibers D1II~D3II as DII at a ratio of 2:5:3, weigh the micro-nanofibers E1II~E3II as EII at a ratio of 2:5:3, mix DII and EII at a ratio of 1:0.95, immerse them in ethanol and mix and disperse them evenly, and then dry them in a vacuum oven to obtain a multi-scale micro-nanofiber network II.

[0027] (6) Three parts of multi-scale micro-nano fiber network II and 97 parts of polyvinylidene fluoride resin were co-extruded to obtain a self-healing polyvinylidene fluoride film II with a thickness of 0.8 mm.

[0028] (7) The self-healing polyvinylidene fluoride film II is melt-blown and roller-pressed with a polyimide release film and a butyl rubber hot melt pressure-sensitive adhesive to obtain a self-healing self-adhesive metal protective film II based on a multi-scale micro-nano fiber network.

[0029] Example 3: A self-healing self-adhesive metal protective film III based on a multi-scale micro-nano fiber network, the preparation process of which is as follows: (1) 100 parts of a trifunctional polyether polyol with a molecular weight of 375, 0.9 parts of a polysiloxane foam stabilizer, 0.2 parts of a T12 catalyst, 0.1 parts of an A33 catalyst and 0.35 parts of water were uniformly dispersed by high-speed stirring as a core layer spinning solution AIII, p-phenylene diisocyanate was used as a core layer spinning solution BIII, 15.5 parts of a polyvinylidene fluoride resin, 3.5 parts of a thermally dissociated latent curing agent and 81 parts of dimethyl sulfoxide were mixed uniformly as a shell layer spinning solution CIII; (2) The core layer spinning solution AIII and the shell layer spinning solution CIII were placed into the core layer syringe and the shell layer syringe of the coaxial electrospinning machine and connected to the needle for coaxial electrospinning. Under the condition of a fixed CIII solution feed rate of 1.0 mL / h, the AIII solution feed rate was adjusted to 0.06 mL / h, 0.2 mL / h and 0.42 mL / h to prepare core-shell structured micro-nanofibers d1III~d3III with diameter distributions of (50~200) nm, (200~800) nm and (1000~2000) nm respectively. (3) Using the core layer spinning solution BIII instead of the core layer spinning solution AIII, referring to step (2), prepare core-shell structured micro-nanofibers e1III~e3III containing a curing agent component with diameter distributions of (50~200) nm, (200~800) nm and (1000~2000) nm of different sizes.

[0030] (4) The multi-scale core-shell structured micro-nanofibers d1III~d3III and e1III~e3III were heated at 80°C for 4 h to obtain the multi-scale core-shell structured micro-nanofibers D1III~D3III and E1III~E3III with shell cross-linked structures.

[0031] (5) Weigh the micro-nanofibers D1III~D3III as DIII in a ratio of 2:5:3, weigh the micro-nanofibers E1III~E3III as EIII in a ratio of 2:5:3, mix DIII and EIII in a ratio of 1:0.95, immerse them in ethanol and mix and disperse them evenly, and then dry them in a vacuum oven to obtain a multi-scale micro-nanofiber network III.

[0032] (6) Three parts of multi-scale micro-nano fiber network III and 97 parts of polyvinylidene fluoride resin were co-extruded to obtain a self-healing polyvinylidene fluoride film III with a thickness of 0.8 mm.

[0033] (7) The self-healing polyvinylidene fluoride film III is melt-blown and rolled with a polyolefin release film and a polyolefin hot-melt pressure-sensitive adhesive to obtain a self-healing self-adhesive metal protective film III based on a multi-scale micro-nano fiber network.

[0034] Example 4: A self-healing self-adhesive metal protective film IV based on a multi-scale micro-nano fiber network, the preparation process of which is as follows: (1) 80 parts of a trifunctional polyether polyol with a molecular weight of 500, 20 parts of a trifunctional polyether polyol with a molecular weight of 700, 1.5 parts of a polysiloxane foam stabilizer, 0.1 parts of a T12 catalyst, 0.2 parts of an A33 catalyst and 0.2 parts of water are uniformly dispersed by high-speed stirring as the core layer spinning solution AIV, isophorone diisocyanate is used as the core layer spinning solution BIV, 13.5 parts of polytrifluorochloroethylene-vinyl ether resin, 3.0 parts of a thermally dissociated latent curing agent and 83.5 parts of N,N-dimethylformamide are mixed uniformly as the shell layer spinning solution CIV; (2) The core layer spinning solution AIV and the shell layer spinning solution CIV were placed into the core layer syringe and the shell layer syringe of the coaxial electrospinning machine and connected to the needle for coaxial electrospinning. Under the condition of a fixed CIV solution feed rate of 1.0 mL / h, the feed rate of the AIV solution was adjusted to 0.06 mL / h, 0.2 mL / h and 0.42 mL / h to prepare core-shell structured micro-nanofibers d1IV~d3IV with diameter distributions of (50~200) nm, (200~800) nm and (1000~2000) nm, respectively; (3) Using the core layer spinning solution BIV instead of the core layer spinning solution AIV, referring to step (2), prepare core-shell structured micro-nanofibers e1IV~e3IV with diameter distributions of (50~200) nm, (200~800) nm and (1000~2000) nm containing a curing agent component of different sizes.

[0035] (4) The multi-scale core-shell structured micro-nanofibers d1IV~d3IV and e1IV~e3IV were heated at 80°C for 4 h to obtain multi-scale core-shell structured micro-nanofibers D1IV~D3IV and E1IV~E3IV with shell cross-linked structures.

[0036] (5) Weigh the micro-nanofibers D1IV~D3IV as DIV in a ratio of 2:5:3, weigh the micro-nanofibers E1IV~E3IV as EIV in a ratio of 2:5:3, mix DIV and EIV in a ratio of 1:1 and immerse them in ethanol to mix and disperse them evenly, and then dry them in a vacuum oven to obtain a multi-scale micro-nanofiber network IV.

[0037] (6) 3.5 parts of the multi-scale micro-nano fiber network IV and 96.5 parts of polyvinylidene fluoride resin were co-extruded to obtain a self-healing polyvinylidene fluoride film IV with a thickness of 0.8 mm.

[0038] (7) The self-healing polyvinylidene fluoride film IV is melt-blown and rolled with a polyester release film and a butyl rubber hot melt pressure-sensitive adhesive to obtain a self-healing self-adhesive metal protective film IV based on a multi-scale micro-nano fiber network.

[0039] Example 5: A self-healing self-adhesive metal protective film V based on a multi-scale micro-nano fiber network, the preparation process of which is as follows: (1) 70 parts of a trifunctional polyether polyol with a molecular weight of 375, 30 parts of a trifunctional polyether polyol with a molecular weight of 1000, 1.0 part of a polysiloxane foam stabilizer, 0.1 parts of a T12 catalyst, 0.3 parts of an A33 catalyst and 0.4 parts of water are mixed and dispersed at high speed to form a core layer spinning solution AV; 80 parts of toluene diisocyanate and 20 parts of toluene diisocyanate trimer are mixed and formed into a core layer spinning solution BV; 12.8 parts of polytetrafluoroethylene chlorovinyl ether resin, 3.3 parts of a thermally dissociated latent curing agent, 60 parts of N,N-dimethylformamide and 23.9 parts of acetone are mixed and formed into a shell layer spinning solution CV; (2) The core layer spinning solution AV and the shell layer spinning solution CV were placed into the core layer syringe and the shell layer syringe of the coaxial electrospinning machine and connected to the needle for coaxial electrospinning. Under the condition of a fixed CV solution feeding rate of 1.0 mL / h, the AV solution feeding rate was adjusted to 0.06 mL / h, 0.2 mL / h and 0.42 mL / h to prepare core-shell structured micro-nanofibers d1V~d3V with diameter distributions of (50~200) nm, (200~800) nm and (1000~2000) nm, respectively; (3) Using the core layer spinning solution BV instead of the core layer spinning solution AV, referring to step (2), prepare core-shell structured micro-nanofibers e1V~e3V containing a curing agent component with diameter distributions of (50~200) nm, (200~800) nm and (1000~2000) nm of different sizes.

[0040] (4) The multi-scale core-shell structured micro-nanofibers d1V~d3V and e1V~e3V were heated at 80°C for 4 h to obtain multi-scale core-shell structured micro-nanofibers D1V~D3V and E1V~E3V with shell cross-linked structures.

[0041] (5) Weigh the micro-nanofibers D1V-D3V as DV in a ratio of 2:5:3, weigh the micro-nanofibers E1V-E3V as EV in a ratio of 2:5:3, mix DV and EV in a ratio of 1:1 and immerse them in ethanol to mix and disperse them evenly, and then dry them in a vacuum oven to obtain a multi-scale micro-nanofiber network V.

[0042] (6) Three parts of the multi-scale micro-nano fiber network V and 97 parts of polyvinylidene fluoride resin were co-extruded to obtain a self-healing polyvinylidene fluoride film V with a thickness of 0.8 mm.

[0043] (7) The self-healing polyvinylidene fluoride film V is melt-blown and rolled with a polyester release film and a polyacrylic hot-melt pressure-sensitive adhesive to obtain a self-healing self-adhesive metal protective film V based on a multi-scale micro-nano fiber network.

[0044] Example 6: A self-healing self-adhesive metal protective film VI based on a multi-scale micro-nano fiber network, the preparation process of which is as follows: (1) 100 parts of a trifunctional polyether polyol with a molecular weight of 500, 1.2 parts of a polysiloxane foam stabilizer, 0.1 parts of a T12 catalyst, 0.1 parts of an A33 catalyst and 0.25 parts of water are mixed and dispersed at high speed to form a core layer spinning solution AVI; 60 parts of isophorone diisocyanate and 40 parts of hexamethylene diisocyanate biuret are mixed and formed into a core layer spinning solution BVI; 14 parts of a polyvinylidene fluoride resin, 3.6 parts of a thermally dissociated latent curing agent, 60 parts of N,N-dimethylacetamide and 22.4 parts of acetone are mixed and formed into a shell layer spinning solution CVI; (2) The core layer spinning solution AVI and the shell layer spinning solution CVI were placed into the core layer syringe and the shell layer syringe of the coaxial electrospinning machine and connected to the needle for coaxial electrospinning. Under the condition of a fixed CVI solution feed rate of 1.0 mL / h, the AVI solution feed rate was adjusted to 0.06 mL / h, 0.2 mL / h and 0.42 mL / h to prepare core-shell structured micro-nanofibers d1VI~d3VI with diameter distributions of (50~200) nm, (200~800) nm and (1000~2000) nm, respectively; (3) Using the core layer spinning solution BVI instead of the core layer spinning solution AVI, referring to step (2), prepare core-shell structured micro-nanofibers e1VI~e3VI containing a curing agent component with diameter distributions of (50~200) nm, (200~800) nm and (1000~2000) nm of different sizes.

[0045] (4) The multi-scale core-shell structured micro-nanofibers d1VI~d3VI and e1VI~e3VI were heated at 80°C for 4 h to obtain multi-scale core-shell structured micro-nanofibers D1VI~D3VI and E1VI~E3VI with shell cross-linked structures.

[0046] (5) Weigh the micro-nanofibers D1VI~D3VI as DVI in a ratio of 2:5:3, weigh the micro-nanofibers E1VI~E3VI as EVI in a ratio of 2:5:3, mix DVI and EVI in a ratio of 1:1, immerse them in ethanol and mix and disperse them evenly, and then dry them in a vacuum oven to obtain a multi-scale micro-nanofiber network VI.

[0047] (6) Three parts of the multi-scale micro-nano fiber network VI and 97 parts of polyvinylidene fluoride resin were co-extruded to obtain a self-healing polyvinylidene fluoride film VI with a thickness of 0.8 mm.

[0048] (7) The self-healing polyvinylidene fluoride film VI is melt-blown and rolled with a polyolefin release film and a polyacrylic hot melt pressure-sensitive adhesive to obtain a self-healing self-adhesive metal protective film VI based on a multi-scale micro-nano fiber network.

[0049] Example 7: A self-healing self-adhesive metal protective film VII based on a multi-scale micro-nano fiber network, the preparation process of which is as follows: (1) 100 parts of a trifunctional polyether polyol with a molecular weight of 700, 0.8 parts of a polysiloxane foam stabilizer, 0.1 parts of a T12 catalyst, 0.3 parts of an A33 catalyst and 0.33 parts of water were uniformly dispersed by high-speed stirring as a core layer spinning solution AVII, hexamethylene diisocyanate trimer was used as a core layer spinning solution BVII, 14.5 parts of a polytetrafluoroethylene chlorovinyl ether resin, 3.5 parts of a thermally dissociated latent curing agent and 82 parts of N,N-dimethylacetamide were mixed uniformly as a shell layer spinning solution CVII; (2) The core layer spinning solution AVII and the shell layer spinning solution CVII were placed into the core layer syringe and the shell layer syringe of the coaxial electrospinning machine and connected to the needle for coaxial electrospinning. Under the condition of a fixed CVII solution feed rate of 1.0 mL / h, the AVII solution feed rate was adjusted to 0.06 mL / h, 0.2 mL / h and 0.42 mL / h to prepare core-shell structured micro-nanofibers d1VII~d3VII with diameter distributions of (50~200) nm, (200~800) nm and (1000~2000) nm, respectively; (3) Using core layer spinning solution BVII instead of core layer spinning solution AVII, referring to step (2), prepare core-shell structured micro-nanofibers e1VII~e3VII containing a curing agent component of different sizes with diameter distributions ranging from (50~200) nm, (200~800) nm and (1000~2000) nm.

[0050] (4) The multi-scale core-shell structured micro-nanofibers d1VII~d3VII and e1VII~e3VII were heated at 80°C for 4 h to obtain the multi-scale core-shell structured micro-nanofibers D1VII~D3VII and E1VII~E3VII with a cross-linked shell structure.

[0051] (5) Weigh the micro-nanofibers D1VII~D3VII as DVII in a ratio of 2:5:3, weigh the micro-nanofibers E1VII~E3VII as EVII in a ratio of 2:5:3, mix DVII and EVII in a ratio of 1:1, immerse them in ethanol and mix and disperse them evenly, and then dry them in a vacuum oven to obtain a multi-scale micro-nanofiber network VII.

[0052] (6) Three parts of the multi-scale micro-nano fiber network VII and 97 parts of polyvinylidene fluoride resin were co-extruded to obtain a self-healing polyvinylidene fluoride film VII with a thickness of 0.8 mm.

[0053] (7) The self-healing polyvinylidene fluoride film VII is melt-blown and rolled with a polyester release film and a polyacrylic hot-melt pressure-sensitive adhesive to obtain a self-healing self-adhesive metal protective film VII based on a multi-scale micro-nano fiber network.

[0054] Example 8: A self-healing self-adhesive metal protective film VIII based on a multi-scale micro-nano fiber network, the preparation process of which is as follows: (1) 100 parts of a trifunctional polyether polyol with a molecular weight of 500, 1.5 parts of a polysiloxane foam stabilizer, 0.1 parts of a T12 catalyst, 0.2 parts of an A33 catalyst and 0.28 parts of water are uniformly dispersed by high-speed stirring as a core layer spinning solution AVIII, toluene diisocyanate trimer is used as a core layer spinning solution BVIII, 13 parts of a polytrifluorochloroethylene-vinyl ether resin, 3.8 parts of a thermally dissociated latent curing agent, 60 parts of dimethyl sulfoxide and 23.2 parts of acetone are uniformly mixed as a shell layer spinning solution CVIII; (2) The core layer spinning solution AVIII and the shell layer spinning solution CVIII were placed into the core layer syringe and the shell layer syringe of the coaxial electrospinning machine and connected to the needle for coaxial electrospinning. Under the condition of a fixed CVIII solution feeding rate of 1.0 mL / h, the feeding rate of AVIII solution was adjusted to 0.06 mL / h, 0.2 mL / h and 0.42 mL / h to prepare core-shell structured micro-nanofibers d1VIII~d3VIII with diameter distributions of (50~200) nm, (200~800) nm and (1000~2000) nm respectively. (3) Using the core layer spinning solution BVIII instead of the core layer spinning solution AVIII, referring to step (2), prepare core-shell structured micro-nanofibers e1VIII~e3VIII containing a curing agent component with diameter distributions of (50~200) nm, (200~800) nm and (1000~2000) nm of different sizes.

[0055] (4) The multi-scale core-shell structured micro-nanofibers d1VIII~d3VIII and e1VIII~e3VIII were heated at 80°C for 4 h to obtain the multi-scale core-shell structured micro-nanofibers D1VIII~D3VIII and E1VIII~E3VIII with a cross-linked shell structure.

[0056] (5) Weigh the micro-nanofibers D1VIII~D3VIII as DVIII in a ratio of 2:5:3, weigh the micro-nanofibers E1VIII~E3VIII as EVIII in a ratio of 2:5:3, mix DVIII and EVIII in a ratio of 1:1, immerse them in ethanol and mix and disperse them evenly, and then dry them in a vacuum oven to obtain a multi-scale micro-nanofiber network VIII.

[0057] (6) 2.8 parts of the multi-scale micro-nano fiber network VIII and 97.2 parts of polyvinylidene fluoride resin were co-extruded to obtain a self-healing polyvinylidene fluoride film VIII with a thickness of 0.8 mm.

[0058] (7) The self-healing polyvinylidene fluoride film VIII is melt-blown and rolled with a polyester release film and a polyacrylic hot melt pressure-sensitive adhesive to obtain a self-healing self-adhesive metal protective film VIII based on a multi-scale micro-nano fiber network.

[0059] Comparative Example 1: Commercially available self-adhesive film A certain brand of commercially available self-adhesive film was used for performance comparison with the examples.

[0060] Comparative Example 2: A self-adhesive film is prepared from pure PVDF film, and the preparation process is as follows: (1) A pure polyvinylidene fluoride film with a thickness of 0.8 mm was obtained by co-extrusion molding using polyvinylidene fluoride resin.

[0061] (2) A self-adhesive metal protective film based on pure PVDF film can be obtained by melt-blowing and roller-pressing pure PVDF film with a polyester release film and a polyacrylic hot-melt pressure-sensitive adhesive.

[0062] Comparative Example 3: A self-healing self-adhesive metal protective film using non-foaming polyurethane as a self-healing medium, the preparation process of which is as follows: (1) 100 parts of a trifunctional polyether polyol with a molecular weight of 500, 0.1 parts of a T12 catalyst, and 0.1 parts of an A33 catalyst are uniformly dispersed as a core layer spinning solution AIX, 60 parts of isophorone diisocyanate and 40 parts of hexamethylene diisocyanate biuret are mixed as a core layer spinning solution BIX, 14 parts of a polyvinylidene fluoride resin, 3.6 parts of a thermally dissociated latent curing agent, 60 parts of N,N-dimethylacetamide, and 22.4 parts of acetone are mixed as a shell layer spinning solution CIX; (2) A multi-scale micro-nano fiber network IX containing a non-foamed polyurethane healing medium was prepared by the same method as in Example 1.

[0063] (3) Three parts of the multi-scale micro-nano fiber network IX and 97 parts of polyvinylidene fluoride resin were co-extruded to obtain a self-healing polyvinylidene fluoride film IX with a thickness of 0.8 mm.

[0064] (4) The self-adhesive metal protective film IX can be obtained by melt-blowing and roller-pressing the self-healing polyvinylidene fluoride film IX with a polyolefin release film and a polyacrylic acid hot melt pressure-sensitive adhesive.

[0065] Comparative Example 4: A self-healing self-adhesive metal protective film using a two-component epoxy resin as a self-healing medium, the preparation process of which is as follows: (1) Take 100 parts of 633 epoxy resin as the core layer spinning solution AX, take D400 polyetheramine as the core layer spinning solution BX, take 14 parts of polyvinylidene fluoride resin, 3.6 parts of thermal dissociation type latent curing agent, 60 parts of N,N-dimethylacetamide and 22.4 parts of acetone and mix them evenly as the shell layer spinning solution CX; (2) A multi-scale micro-nano fiber network X containing epoxy resin healing medium was prepared by the same method as in Example 1.

[0066] (3) Three parts of the multi-scale micro-nano fiber network X and 97 parts of polyvinylidene fluoride resin were co-extruded to obtain a self-healing polyvinylidene fluoride film X with a thickness of 0.8 mm.

[0067] (4) The self-adhesive metal protective film X can be obtained by melt-blowing and roller-pressing the self-healing polyvinylidene fluoride film X with a polyolefin release film and a polyacrylic acid hot melt pressure-sensitive adhesive.

[0068] Comparative Example 5: A self-healing self-adhesive metal protective film using only large-size self-healing fibers, the preparation process of which is as follows: (1) The preparation process of core layer spinning solution AIV, core layer spinning solution BIV and shell layer spinning solution CIV is as described in Example 4.

[0069] (2) The core layer spinning solution AIV and the shell layer spinning solution CIV were placed into the core layer syringe and the shell layer syringe of the coaxial electrospinning machine and connected to the needle for coaxial electrospinning. Under the condition of a fixed CIV solution feed rate of 1.0 mL / h, by adjusting the AIV solution feed rate to 0.42 mL / h, core-shell structure fibers dXI with a diameter distribution of (1000-2000) nm wrapped with the polyurethane main component were prepared. (3) Using the core layer spinning solution BIV instead of the core layer spinning solution AIV, refer to step (2) to prepare the core-shell structure fiber eXI containing the curing agent component with a diameter distribution of (1000~2000) nm.

[0070] (4) The core-shell structure fibers dXI and eXI were heated at 80°C for 4 h to obtain core-shell structure fibers DXI and EXI with shell cross-linked structures. DXI and EXI were mixed in a ratio of 1:1 and immersed in ethanol to mix and disperse evenly, and then dried in a vacuum oven to obtain a fiber network XI.

[0071] (5) 3.5 parts of the fiber network XI and 96.5 parts of the polyvinylidene fluoride resin were co-extruded to obtain a self-healing polyvinylidene fluoride film XI with a thickness of 0.8 mm.

[0072] (6) The self-healing polyvinylidene fluoride film XI is melt-blown and roller-pressed with a polyester release film and a butyl rubber hot melt pressure-sensitive adhesive to obtain a self-healing self-adhesive metal protective film XI.

[0073] Comparative Example 6: A self-healing self-adhesive metal protective film using only small-sized self-healing fibers, the preparation process of which is as follows: (1) The preparation process of core layer spinning solution AIV, core layer spinning solution BIV and shell layer spinning solution CIV is as described in Example 4.

[0074] (2) The core layer spinning solution AIV and the shell layer spinning solution CIV were placed into the core layer syringe and the shell layer syringe of the coaxial electrospinning machine and connected to the needle for coaxial electrospinning. Under the condition of a fixed CIV solution feed rate of 1.0 mL / h, the AIV solution feed rate was adjusted to 0.06 mL / h to prepare core-shell structure fibers dXII with a diameter distribution of (50-200) nm wrapped with the polyurethane main component. (3) Using the core layer spinning solution BIV instead of the core layer spinning solution AIV, refer to step (2) to prepare core-shell structure fibers eXII containing a curing agent component with a diameter distribution of (50~200) nm.

[0075] (4) The core-shell structure fibers dXII and eXII were heated at 80°C for 4 h to obtain core-shell structure fibers DXII and EXII with a shell cross-linked structure. DXII and EXII were mixed in a ratio of 1:1 and immersed in ethanol to mix and disperse evenly, and then dried in a vacuum oven to obtain a fiber network XII.

[0076] (5) 3.5 parts of the fiber network XII and 96.5 parts of the polyvinylidene fluoride resin were co-extruded to obtain a self-healing polyvinylidene fluoride film XII with a thickness of 0.8 mm.

[0077] (6) The self-healing polyvinylidene fluoride film XII is melt-blown and roller-pressed with a polyester release film and a butyl rubber hot melt pressure-sensitive adhesive to obtain a self-healing self-adhesive metal protective film XII.

[0078] Comparative Example 7: A self-healing self-adhesive metal protective film using dual-size distribution self-healing fibers, the preparation process of which is as follows: (1) The core layer spinning solution AII, the core layer spinning solution BII and the shell layer spinning solution CII are prepared as described in Example 2; (2) The core layer spinning solution AII and the shell layer spinning solution CII were placed into the core layer syringe and the shell layer syringe of the coaxial electrospinning machine and connected to the needle for coaxial electrospinning. Under the condition of a fixed CII solution feed rate of 1.0 mL / h, the feed rate of AII solution was adjusted to 0.06 mL / h and 0.42 mL / h to prepare core-shell structured micro-nanofibers d1XIII and d2XIII with diameter distributions of (50-200) nm and (1000-2000) nm, respectively. (3) Using the core layer spinning solution BII instead of the core layer spinning solution AII, referring to step (2), prepare core-shell structured micro-nanofibers e1XIII and e2XIII containing a curing agent component of different sizes with a diameter distribution of (50-200) nm and (1000-2000) nm.

[0079] (4) The core-shell structured micro-nanofibers d1XIII, d2XIII, e1XIII and e2XIII were heated at 80°C for 4 h to obtain core-shell structured micro-nanofibers D1XIII, D2XIII, E1XIII and E2XIII with a cross-linked shell structure.

[0080] (5) Weigh the micro-nanofibers D1XIII and D2XIII as DXIII in a ratio of 1:1, weigh the micro-nanofibers E1XIII and E2XIII as EXIII in a ratio of 1:1, mix DXIII and EXIII in a ratio of 1:0.95, immerse them in ethanol and mix and disperse them evenly, and then dry them in a vacuum oven to obtain the micro-nanofiber network XIII.

[0081] (6) Three parts of the multi-scale micro-nano fiber network XIII and 97 parts of polyvinylidene fluoride resin were co-extruded to obtain a self-healing polyvinylidene fluoride film XIII with a thickness of 0.8 mm.

[0082] (7) The self-healing polyvinylidene fluoride film XIII is melt-blown and rolled with a polyimide release film and a butyl rubber hot melt pressure-sensitive adhesive to obtain a self-healing self-adhesive metal protective film XIII based on a multi-scale micro-nano fiber network.

[0083] Effect description: The self-healing self-adhesive metal protective film based on multi-scale micro-nano fiber network prepared in Examples 1-8 of the present invention was used to conduct performance tests and comparisons with the comparative film materials of Comparative Examples 1-7. The peel strength, mechanical properties, durability and self-healing properties of the self-adhesive film materials under different conditions were tested, where micro-scale self-healing refers to the self-healing effect of micro-cracks made by tensile tests, and macro-scale self-healing refers to the self-healing effect of macro-cracks made by cutting tests. Both are expressed in terms of appearance effect and closed area, and the number of repeated self-healing refers to the number of times macro-self-healing can be achieved. The relevant test results have been organized into Table 1: Table 1 Performance test results of self-adhesive metal protective film Sample No. Peel strength (N / cm) Tensile strength (MPa) Elongation at break (%) Salt spray 1500h Micro-scale self-healing Macro-scale self-healing Repeat self-healing times Example 1 2.5 12.0 147.5 No change Healed 95% Healed 92% 15 Example 2 2.3 11.6 137.0 No change Healed 93% Healed 91% 16 Example 3 2.2 13.5 148.2 No change Healed 92% Healed 88% 18 Example 4 2.3 12.8 142.8 No change Healed 92% Healed 93% 15 Example 5 2.1 11.4 136.6 No change Healed 96% Healed 90% 16 Example 6 2.4 12.3 144.5 No change Healed 98% Healed 89% 18 Example 7 2.5 12.5 138.9 No change Healed 91% Healed 91% 17 Example 8 2.2 13.1 153.2 No change Healed 95% Healed 92% 16 Comparative Example 1 0.6 5.8 68.8 Yellowing No healing No healing 0 Comparative Example 2 2.2 10.8 125.6 No change No healing No healing 0 Comparative Example 3 2.1 11.6 135.5 No change Healing 75% Healed 62% 3 Comparative Example 4 2.0 12.3 144.5 No change Healed 68% Heal 50% 2 Comparative Example 5 2.2 9.8 123.8 No change Healing 32% Healing 65% 12 Comparative Example 6 2.1 10.2 118.9 No change Healing 70% Healing 40% 6 Comparative Example 7 2.2 10.5 125.3 No change Healed 78% Healed 72% 10 From the data in Table 1, it can be seen that the self-healing self-adhesive metal protective film based on the multi-scale micro-nano fiber network prepared in the embodiment has high bonding performance, strong tensile strength and toughness, and can achieve no change in the salt spray environment for 1500h, and has strong practical performance. This is mainly because the PVDF resin extrusion mold used has high mechanical properties and durability, and has good compatibility with the self-adhesive layer. Therefore, it is suitable for long-term protection of steel structures. In terms of self-healing of material damage, the embodiments can achieve good self-healing effects, and the self-healing ability for micro cracks can reach 91%~98%, and the self-healing ability for macro cracks can reach 88%~92%. This is partly because the multi-scale micro-nano composite self-healing fiber network can achieve a response to cracks of different sizes, and on the other hand, it is also because the self-healing medium therein is a polyurethane with micro-foaming properties, which has a strong healing and filling ability. In terms of repeated self-healing performance, the embodiments can achieve more than 15 self-healing times. This is because the micro-foamed polyurethane can achieve crack healing under relatively small dosage conditions and generate a certain expansion pressure to inhibit excessive leakage of the healing medium, thus achieving multiple self-healing performance. The above test results show that the embodiments have good performance in long-term protection effect and self-healing performance, and have strong practical value.

[0084] Comparative Example 1 is a commercially available self-adhesive film. Due to the poor quality of the film material and the self-adhesive, its performance in terms of bonding, strength and durability is poor, and it does not have self-healing properties, making it difficult to meet the requirements of long-term protection and durable protection. Comparative Example 2 is a self-adhesive film prepared using pure PVDF extruded film. It has significantly improved performance in terms of bonding, strength and durability, but since it does not contain a self-healing fiber network, it also does not have a self-healing function. It is easy to fail to protect due to cracking damage under conditions such as stress from the external environment.

[0085] Comparative Examples 3 and 4 are self-healing self-adhesive metal protective film materials prepared using conventional polyurethane and epoxy resin as self-healing media. Although they have a certain degree of self-healing performance, since the medium is a non-foaming material, it itself will even have a certain shrinkage during the curing process, resulting in its healing performance being lower than that of the embodiment. Moreover, since a single self-healing requires a large amount of medium reaction, the number of self-healing that can be achieved is relatively small, and long-term use is also insufficient.

[0086] Comparative Examples 5 and 6 are self-healing self-adhesive films prepared by self-healing fiber networks obtained by using large-size fibers or small-size fibers alone. It can be seen that, on the one hand, due to the single fiber size, it will have a certain strength impact on the substrate itself, resulting in a decrease in strength and toughness. In addition, it is difficult for single-size fibers to achieve effective response to multi-scale cracks, and it has obvious deficiencies in the repair performance of size-mismatched cracks, which also causes the applicability of the protective film to decrease. Comparative Example 7 is a self-healing self-adhesive film prepared by a self-healing fiber network obtained by using 1:1 large and small size graded fibers. From the test results, it can be seen that due to insufficient size matching, the formation of the fiber network is not perfect, and the two-graded fibers are difficult to achieve a good response to multi-scale cracks, which is quite different from the embodiments in terms of mechanical properties and self-healing properties.

[0087] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A self-healing and self-adhesive metal protective film based on a multi-scale micro-nano fiber network, characterized in that A self-adhesive protective film material consisting of a self-healing polyvinylidene fluoride film containing a multi-scale micro-nano fiber network, a self-adhesive layer and a release film layer; wherein the multi-scale micro-nano fiber network is composed of micro-nano fibers with a core-shell structure prepared by coaxial electrospinning using fluorocarbon resin as the wall material and a micro-foamed polyurethane main agent and a curing agent as the core material; wherein the fiber diameter size distribution in the multi-scale micro-nano fiber network is (50~200)nm:(200~800)nm:(1000~2000)nm=2:5:

3.

2. According to claim 1, a self-healing and self-adhesive metal protective film based on a multi-scale micro-nano fiber network is characterized in that The method for preparing the multi-scale micro-nano fiber network comprises the following steps: (1) taking the micro-foamed polyurethane main agent as the core layer spinning solution A, the micro-foamed polyurethane curing agent as the core layer spinning solution B, and the fluorocarbon resin solution as the shell layer spinning solution C; (2) The core layer spinning solution A and the shell layer spinning solution C were placed into the core layer syringe and the shell layer syringe of the coaxial electrospinning machine and connected to the needle for coaxial electrospinning. Under the condition of a fixed feed rate of C solution at (0.95-1.05) mL / h, the feed rate of A solution was adjusted to (0.05-0.10) mL / h, (0.15-0.25) mL / h and (0.35-0.45) mL / h to prepare core-shell structured micro-nanofibers d1-d3 with diameter distributions of (50-200) nm, (200-800) nm and (1000-2000) nm respectively. (3) Using core layer spinning solution B instead of core layer spinning solution A, referring to step (2), prepare core-shell structured micro-nano fibers e1-e3 with diameter distributions of (50-200) nm, (200-800) nm and (1000-2000) nm containing curing agent components of different sizes; (4) The multi-scale core-shell structured micro-nanofibers d1-d3 and e1-e3 were heated at 80°C for 4 h to obtain the multi-scale core-shell structured micro-nanofibers D1-D3 and E1-E3 with a shell cross-linked structure; (5) Weigh the micro-nano fibers D1-D3 as D in a ratio of 2:5:3, weigh the micro-nano fibers E1-E3 as E in a ratio of 2:5:3, mix D and E in a ratio of 1:(0.9-1.2), immerse them in ethanol and mix and disperse them evenly, and then dry them in a vacuum oven to obtain a multi-scale micro-nano fiber network.

3. A method for preparing a multi-scale core-shell structured micro-nano fiber according to claim 2, characterized in that The micro-foaming polyurethane main agent is prepared by uniformly dispersing a polyether polyol, a foam stabilizer, a catalyst and water through high-speed stirring, wherein the amounts of the stabilizer, the catalyst and the water are 0.5-2%, 0.05-0.5% and 0.1-0.5% respectively, based on the mass of the polyether polyol; wherein the polyether polyol is at least one of trifunctional hydrophobic polyether polyols with a relative molecular mass of 300-1200, the foam stabilizer is a polysiloxane stabilizer, and the catalyst is at least one of A33 and T12; wherein the micro-foaming polyurethane curing agent is toluene diisocyanate, isophorone diisocyanate, p-phenylene diisocyanate, toluene diisocyanate The fluorocarbon resin solution is composed of at least one of a fluorocarbon resin, a latent curing agent and a solvent, wherein the contents of the fluorocarbon resin, the latent curing agent and the solvent are 12-16%, 3-4% and 80-85% respectively, wherein the fluorocarbon resin is at least one of polyvinylidene fluoride resin, polytrifluorochloroethylene-vinyl ether resin and polytetrafluorochloroethylene-vinyl ether resin, the latent curing agent is a thermally dissociated latent curing agent, and the solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide and acetone.

4. The method for preparing a multi-scale core-shell structured micro-nano fiber according to claim 2, characterized in that In the coaxial electrospinning process, the spinning distance is 12-20 cm, the spinning voltage is 11-18 kV, the ambient temperature is 20-28° C., and the ambient humidity is 30%-70% RH.

5. The self-healing and self-adhesive metal protective film based on a multi-scale micro-nano fiber network according to claim 1, characterized in that The self-healing polyvinylidene fluoride film containing a multi-scale micro-nano fiber network is a film obtained by co-extrusion molding of a multi-scale micro-nano fiber network and a polyvinylidene fluoride resin; wherein the amount of the multi-scale micro-nano fiber network is 2-5% of the amount of the polyvinylidene fluoride resin; wherein the thickness of the film is 0.5-1.5 mm.

6. The self-healing and self-adhesive metal protective film based on a multi-scale micro-nano fiber network according to claim 1, characterized in that The preparation method is as follows: (1) tensioning the release film and melt-blowing a hot-melt pressure-sensitive adhesive on the release film; (2) compounding it with a self-healing polyvinylidene fluoride film containing a multi-scale micro-nano fiber network, and rolling it together to obtain a self-healing self-adhesive metal protective film based on a multi-scale micro-nano fiber network.

7. A method for preparing a self-healing self-adhesive metal protective film based on a multi-scale micro-nano fiber network according to claim 6, characterized in that The release film is one of a polyolefin release film, a polyimide release film, and a polyester release film; wherein the hot melt pressure-sensitive adhesive is one of a polyacrylic hot melt pressure-sensitive adhesive, a polyolefin hot melt pressure-sensitive adhesive, a polystyrene hot melt pressure-sensitive adhesive, and a butyl rubber hot melt pressure-sensitive adhesive.

8. Application of a self-healing and self-adhesive metal protective film based on a multi-scale micro-nano fiber network as claimed in claim 1 as a protective material or rust repair material for building structures such as steel structure bridges, factory buildings, curtain walls, etc.

Citation Information

Patent Citations

  • Preparation method of self-healing film based on layer-by-layer assembled hollow multilayer nanocapsules

    CN103755156B

  • A PVDC high-barrier co-extruded self-adhesive film for military protection and its preparation method

    CN112831121B

  • Self-repairing shell-core nanofiber membrane, preparation method and application

    CN115387030A